2009
DOI: 10.2353/ajpath.2009.090126
|View full text |Cite
|
Sign up to set email alerts
|

Reduced Phosphoinositide 3-Kinase (p110α) Activation Increases the Susceptibility to Atrial Fibrillation

Abstract: Atrial fibrillation (AF) is the most common sustained arrhythmia presenting at cardiology departments. A limited understanding of the molecular mechanisms responsible for the development of AF has hindered treatment strategies. The purpose of this study was to assess whether reduced activation of phosphoinositide 3-kinase (PI3K, p110␣) makes the compromised heart susceptible to AF. Risk factors for AF, including aging, obesity, and diabetes, have been associated with insulin resistance that leads to depressed/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

4
145
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 160 publications
(154 citation statements)
references
References 61 publications
4
145
5
Order By: Relevance
“…The inhibition of myocardial PI3K has the potential to induce cardiac dysfunction by decreasing cardiac contractility and increasing susceptibility to cardiac arrhythmias 28. Loss of PI3K activity is associated with prolonged APD and QT intervals, whereas an increase in its activity markedly decreases atrial fibrosis 29, 30. Therefore, PI3K, a cardioprotective protein, is associated with the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…The inhibition of myocardial PI3K has the potential to induce cardiac dysfunction by decreasing cardiac contractility and increasing susceptibility to cardiac arrhythmias 28. Loss of PI3K activity is associated with prolonged APD and QT intervals, whereas an increase in its activity markedly decreases atrial fibrosis 29, 30. Therefore, PI3K, a cardioprotective protein, is associated with the development of AF.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, new therapeutic strategies to protect the heart in the setting of diabetes are greatly needed. We have previously demonstrated that increased activation of phosphoinositide 3-kinase (PI3K)(p110α) in the heart is protective in pathological settings in which the heart is subjected to a localised cardiac insult such as aortic constriction (pressure overload) or coronary artery ligation (myocardial infarction) [12][13][14]. However, whether PI3K (p110α) can protect the heart against diabetic cardiomyopathy caused by global hyperglycaemia is unknown.…”
Section: Introductionmentioning
confidence: 99%
“…In brief, the model was generated by breeding a cardiac-specific Tg mouse with a failing heart because of dilated cardiomyopathy (DCM, induced with increased activity of mammalian sterile 20-like kinase 1, Mst1; a kinase activated by clinically important pathologic insults such as ischaemia/ reperfusion 21 ) with a cardiac-specific Tg mouse with reduced phosphoinositide 3-kinase (PI3K; because of expression of a dominant negative PI3K (dnPI3K) mutant 22 ). Risk factors for HF and AF, including ageing, obesity and diabetes, have been associated with insulin resistance that can lead to depressed/ defective PI3K signalling [23][24][25] , and PI3K activity was also depressed in atrial tissue from patients with AF 20 . Reducing PI3K in the mouse model with DCM accelerated the HF phenotype based on the following findings: additional systolic dysfunction, substantial atrial enlargement, increased fibrosis and elevated lung weights 20 .…”
mentioning
confidence: 99%
“…Risk factors for HF and AF, including ageing, obesity and diabetes, have been associated with insulin resistance that can lead to depressed/ defective PI3K signalling [23][24][25] , and PI3K activity was also depressed in atrial tissue from patients with AF 20 . Reducing PI3K in the mouse model with DCM accelerated the HF phenotype based on the following findings: additional systolic dysfunction, substantial atrial enlargement, increased fibrosis and elevated lung weights 20 . At 4 months of age, the HF þ AF model was also associated with electrocardiogram (ECG) abnormalities including intermittent/episodic AF (irregular heart rhythm with loss of P waves confirmed by intracardiac ECG recordings) 20 .…”
mentioning
confidence: 99%
See 1 more Smart Citation